2004
DOI: 10.1152/japplphysiol.01074.2003
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific changes in platelet aggregation and secretion with sexual maturity in pigs

Abstract: Cardiovascular disease may begin early in adolescence. Platelets release factors contributing to vascular disease. Experiments were designed to test the hypothesis that hormonal transitions associated with sexual maturity differentially affect platelet aggregation and secretion in males and females. Platelets were collected from juvenile (2-3 mo) and sexually mature (adult; 5-6 mo) male and female pigs (n=8/group). Maturation was evidenced by increased weight of reproductive tissue and changes in circulating l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 42 publications
2
38
1
Order By: Relevance
“…Studies have shown that female sex hormones exert negative effect on platelet aggregation [16][17][18] , but the effect was not remarkably increased after aspirin administration in our research, possibly because of the females being partial responders of aspirin 19 or some other compensatory mechanism in their body not yet known. For instance, cyclooxygenase activity was found to be higher after overiectomy but lower after castration 20 , indicating the probable role of female sex hormones in depressing cyclooxygenase activity.…”
contrasting
confidence: 73%
“…Studies have shown that female sex hormones exert negative effect on platelet aggregation [16][17][18] , but the effect was not remarkably increased after aspirin administration in our research, possibly because of the females being partial responders of aspirin 19 or some other compensatory mechanism in their body not yet known. For instance, cyclooxygenase activity was found to be higher after overiectomy but lower after castration 20 , indicating the probable role of female sex hormones in depressing cyclooxygenase activity.…”
contrasting
confidence: 73%
“…Some authors suggest that platelet aggregability changes with sexual maturity differently in females and males. Jayachandran et al [42] reported sex related differences in platelet aggregation with sexual maturation, showing decreases in females and increases in males with maturity.…”
Section: Discussionmentioning
confidence: 99%
“…Specific protein bands on films (chemiluminescence detection) and membranes (colorimetric determination) were scanned and digitized by positive segment analysis using UN-SCAN-IT (30). An equal amount of proteins transferred from gel to membrane was determined by ␀-actin expression (29). Average pixel values from each individual blot were used for statistical analysis.…”
Section: Methodsmentioning
confidence: 99%